In silico analysis of optimum photon energy spectra and beam parameters for iodine nanoparticle–aided orthovoltage radiation therapy of brain tumors. (June 2023) - Mesbahi, Asghar; Sadeghian, Maryam; Mesbahi, Aisan; Smilowitz, Henry M; Hainfeld, James F
In this study, the effect of photon energy spectra on the dose enhancement factor (DEF) and other influencing parameters such as skull–tumor dose ratios were estimated for a confined tumor loaded with iodine nanoparticles (INPs). A mathematical brain phantom with a brain tumor was simulated by the MCNP6 Monte Carlo code. A validated commercial computed tomography model consisting of an X-ray tube, Al–Cu filters, and collimators was used to simulate the rotational conformal treatment of the tumor. INPs with a diameter of 20 nm and concentrations of 10–50 mg/g were introduced inside the tumor as homogenously distributed spherical particles. The dose distribution inside the phantom was scored for several orthovoltage beams with the peak voltages of 140, 200, and 320 kVp as well as two 3.5 and 6 MV megavoltage beams. A significant rise of DEF values with nanoparticle (NP) concentration for orthovoltage beams is revealed; no significant dose enhancement was obtained for megavoltage beams. The highest DEF and skull–tumor dose ratio were obtained for the 140 kVp beam which decreased with the number of directional fields. The clinically optimal plan for a brain tumor, with high DEFs of 2.81–2.24 and acceptable skull–tumor dose ratios of 0.61–0.51, would be feasible for treatment using 200 and 320 kVp beams, an iodine concentration of 20 mg/g, and 8–15 fields. Our calculations show that clinically significant radiation dose enhancements can be obtained for tumors loaded with INPs using orthovoltage beams. Optimal treatment regimens are feasible using a proper selection of photon beam spectrum and sufficient numbers of cross-firing beams. The limiting effect of skull bone could be minimized by increasing the number of radiation fields and the use of higher quality of orthovoltage beams.